2011
DOI: 10.1109/tnn.2011.2168568
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Multitask Classification With Gaussian Process Priors

Abstract: We present a novel approach to multitask learning in classification problems based on Gaussian process (GP) classification. The method extends previous work on multitask GP regression, constraining the overall covariance (across tasks and data points) to factorize as a Kronecker product. Fully Bayesian inference is possible but time consuming using sampling techniques. We propose approximations based on the popular variational Bayes and expectation propagation frameworks, showing that they both achieve excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…The task covariance matrix K t can be restricted to a correlation matrix by enforcing a unit diagonal (proper range of off-diagonal elements is ensured by positive definiteness of K t ) [31,32]. We refer to this method as MTL-COR (correlation matrix).…”
Section: Multi-task Learningmentioning
confidence: 99%
“…The task covariance matrix K t can be restricted to a correlation matrix by enforcing a unit diagonal (proper range of off-diagonal elements is ensured by positive definiteness of K t ) [31,32]. We refer to this method as MTL-COR (correlation matrix).…”
Section: Multi-task Learningmentioning
confidence: 99%
“…2009), financial time series (Niu and Wang 2014), among others. Inspired by the philosophy behind the multi-task learning framework originated in Machine learning (Caruana 1997;Bakker and Heskes 2003;Bonilla et al 2007;Skolidis and Sanguinetti 2011), we propose in this paper a patient-dependent classification system for basal ganglia identification. The idea behind multi-task learning is that by learning simultaneously different but related tasks, it is possible to increase the performance of a learning algorithm (Argyriou et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We also use the ICM covariance in a multi-task Gaussian process classifier as introduced in Skolidis and Sanguinetti (2011), and refer to this method as MI. 9 In Skolidis and Sanguinetti (2011), the authors use a probit model for relating the observed data y, with the un-observed variables f .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ref. , graph-based SRC is a within-network classification task and it can be categorized into two main groups: collective inference Macskassy and Provost, 2007;Skolidis and Sanguinetti, 2011;Zhang and Mao, 2008;Zhang et al, 2011Zhang et al, , 2006Zhu et al, 2007) and graph-based semisupervised learning (Chapelle et al, 2006;Silva and Zhao, 2012a,b,c;Zhu, 2005a). In both cases, the labels are propagated from pre-labeled vertices to unlabeled vertices considering the local relationships or certain smoothness criteria.…”
Section: Motivationmentioning
confidence: 99%